At what age group blood pressure discontinue to increase? An assessment using change-point analysis (Faculty of Medicine Universitas Indonesia, 2010)
Aim To study at what age group blood pressure ceases to increase for women and men. Methods Applying change-point technique, we used our existing database - mega base-line cross-sectional Hulu Langat Health Study that was initiated in 2000 - to locate the most appropriate age limit in planning promotive, preventive and controlling strategies against systolic hypertension. Results Systolic hypertension was found to be constantly increasing for both gender right from the early age until the middle age group. However, women achieved the systolic peak 15 years earlier (at 41-45 years old) than men (at 56-60 years old). Systolic blood pressure was steadily declined after the peak. Conclusions Hypertension intervention, we recommend age before 40 (women) and 55 (men) be the most appropriate period to apply various public health intervention, after that, the action must be exclusively curative. (Med J Indones 2010; 19:136-41)